International Humanitarian Law Amid The Gaza Crisis: Power Asymmetry, Civil Violations, and Global Accountability Imbalance - Komarudin, Dedi; Kismanto, Totok Prio; Susilo, Tarsisius; Budi, I Ketut Setia; Iskandar, Yulian (Universitas Muhammadiyah Tangerang, 2025)
The Israel–Palestine conflict is one of the longest-standing conflicts that has drawn significant international attention, especially concerning the application of International Humanitarian Law (IHL). This article aims to analyze the dynamics of implementing core IHL principles, such as the principles of proportionality, distinction, and the protection of civilians, in the ongoing armed conflict in the Gaza Strip and West Bank. Through a qualitative approach with document analysis of official reports from the UN, ICRC, and international NGOs, various violations of IHL norms were identified, which had a significant impact on civilians, including attacks on medical facilities, schools, and restrictions on humanitarian access. Additionally, this article highlights enforcement challenges, such as politicization at the UN Security Council and the weakness of international sanctions mechanisms. The findings underscore the importance of strengthening the international legal system and the role of the global community in promoting accountability and civilian protection. This article is expected to contribute academically to contemporary discussions on humanitarian law and human rights in conflict zone.Keywords: International Humanitarian Law, Israel–Palestine, Civilians, Human Rights Violations, Armed Conflict.